Late-Onset Calorie Restriction Improves Lipid Metabolism and Aggravates Inflammation in the Liver of Old Wistar Rats - Teofilović, Ana; Vratarić, Miloš; Veličković, Nataša; Vojnović Milutinović, Danijela; Mladenovic, Aleksandra; Prvulovic, Milica; Djordjevic, Ana (Frontiers in Nutrition, 2022)
Aging is a progressive process that could disturb metabolic homeostasis in the liver via ectopic lipid accumulation, oxidative stress and deterioration of inflammatory response. Although calorie restriction (CR) is recognized as beneficial for lifespan and healthspan prolongation it is still unclear how late-onset CR, characterized by late beginning and short duration, affects age related processes. The aim of this study was to examine how late-onset CR-induced metabolic adjustments impact lipid status and inflammation in the liver of old rats. The experiments were conducted on aging male Wistar rats fed ad libitum (AL) or exposed to late-onset CR (60% of AL daily intake) from 21st to 24th month. The results showed that late-onset CR reduces body weight, visceral adipose tissue and liver mass, and triglyceride levels when compared to old animals on AL diet. The ameliorating effects of CR on lipid metabolism include increased activity of AMP-activated protein kinase, suppressed de novo fatty acid synthesis, stimulated β-oxidation, decreased lipotoxicity, and limited triglyceride synthesis and packaging in the liver. Restricted diet regime however, does not improve expression of antioxidant enzymes, while leads to progression of age-related inflammation in the liver, partially through lower corticosterone concentration and decreased activation of glucocorticoid receptor. In conclusion, late-onset CR is able to restore age-related disbalance of lipid metabolism in the liver, but has negative impact on hepatic inflammatory status, implying that type of the diet for older individuals must be balanced and chosen carefully with appropriate duration and start point.